Hydrophilic modification of polypropylene ultrafiltration membrane by air‐assisted polydopamine coating. (4th February 2019) - Wardani, Anita Kusuma; Ariono, Danu; Subagjo,; Wenten, I Gede
Abstract : Coating by a mussel inspired polydopamine (PDA) is a simple and promising strategy to modify the hydrophilicity of polymer membrane surfaces. In this work, PDA coating was used to modify polypropylene (PP) ultrafiltration hollow fiber membrane. PDA coating parameters, ie, solution concentration and coating time were varied, and the effect of those parameters on membrane morphology, porosity, water contact angle, and pure water flux was investigated. In addition, air‐assisted PDA coating process was also conducted by channelling the air through PP membrane to avoid pore blocking and prevent water flux decline. The results showed that PDA coating successfully improved the hydrophilicity of PP membrane indicated by the decrease of water contact angle from 110° to 67° after coated by 3 g/L of PDA solution for 3 hours. The addition of air permeation on membrane lumen also increased pure water flux up to 511.2 L/m 2 .h, a 270% increase from unmodified PP membrane. It might be associated to the pore blocking prevention that has been proven by SEM image and the membrane porosity that was increased about 4%.